Social Innovation, Circularity and Energy Transition for Environmental, Social and Governance (ESG) Practices—A Comprehensive Review - Popescu, Catalin; Hysa, Eglantina; Kruja, Alba; Mansi, Egla (Energies (Basel), 2022)
It has been extensively debated how social innovation, circularity, and energy transition may all be considered environmental, social, and governance (ESG) components from a sustainability perspective. To comprehend the conceptual development of this subject in the academic literature, few studies, however, tackle the problems above by reviewing earlier research on the subject. By developing the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) technique, this study aims to address the current and anticipated advancements in social innovation, energy transition, and circularity. As a result, we create two metasynthesis analyses related to “social innovation–energy transition” and “social innovation–circularity.” In the first analysis, the three databases Web of Science, Scopus, and JSTOR had a total of 1767 studies and reports, and in the second analysis, we reviewed the work from a total of 466 studies and reports. We emphasize that implementing environmental, social, and governance (ESG) practices require social innovation, circularity, and energy transition. The study’s key contributions are the five cluster themes classification for the two metasynthesis analyses, which point to potential future directions for both firms and governments to pursue some macro-level goals concerning energy transition and circularity through social innovation.